Safety and efficacy of surgically performed continuous superficial serratus anterior plane block in uniportal video-assisted thoracic surgery - Giovanni Punzo; Dania Nachira; Giuseppe Calabrese; Chiara Cambise; Maria Teresa Congedo; Maria Letizia Vita; Elisa Meacci; Stefano Margaritora (Journal of Minimal Access Surgery)
Introduction: The ‘surgically performed’ continuous superficial serratus anterior plane block (continuous s-SAPB) was never described before in uniportal video-assisted thoracic surgery (uniportal VATS) surgery. The aim of the study was to evaluate the safety and efficacy of the technique. Patients and Methods: Between March 2022 and April 2023, 50 patients, undergone uniportal VATS surgery at our thoracic surgery department, were scheduled for a surgically performed continuous s-SAPB as post-operative analgesia protocol. Results: The mean execution time for the block was 3.92 ± 2.56 min. Ten patients (20%) required morphine for a visual analogue scale (VAS) score >4 immediately after surgery. The recorded VAS score at chest tube removal was 1.87 ± 1.41, whereas 2 h after the manoeuvre was 0.42 ± 0.72. No complication related to block insertion was recorded. The onset of chronic pain was observed in a total of 2 patients (4%). Conclusions: The surgically performed continuous s-SAPB in uniportal VATS seems to be safe and easy to perform, and it provides a satisfactory analgesic effect.